Michigan Ophthalmology Pipeline: Exploring a Mentorship Model to Increase Diversity in Ophthalmology - Shaner, Mason A.; Kaplan, Ariane; Sesi, Christopher; Manjunathan, Abhishek; Lacy, Gabrielle D.; Prisk, Lauren; Crear, Jara; Sugar, Alan; Elam, Angela; Mian, Shahzad I. (Journal of Academic Ophthalmology, 2020)
Background Ethnic concordance between physicians and patients improves compliance and therapeutic benefit. Current literature shows a lack of diversity within ophthalmology. Thus, we aimed to develop a longitudinal mentorship program between first year ophthalmology residents (PGY2s) and first year medical students (M1s) coming from minority communities underrepresented in medicine (URM) to provide early exposure to the field.Methods M1 members of URM organizations were recruited and paired with PGY2 ophthalmology residents in a mentorship program between 2017 and 2019. All participants were surveyed twice annually.Results All 2017 M1s stated increased interest in ophthalmology, felt “satisfied” or “very satisfied” with the program, and completed all requirements. At the year-end, the mean educational value of the program for 2017 M1s was rated 4.33/5, and interest in ophthalmology 4.67/5. Quality of the clinical experiences for 2017 PGY2s 3.5/5, and the overall effectiveness of the program 3.5/5. At the year-end, the average educational value of the program for 2018 M1s was 4.4/5, and interest in ophthalmology 4.0/5. Quality of the clinical experiences for 2018 PGY2s was 3.1/5, and the overall effectiveness of the program was 3.4/5.Conclusion Our “pipeline” program represents an ongoing effort to increase URM interest in ophthalmology. Continued assessment to identify areas for growth and improvement can optimize the program to aid other programs in initiating efforts to tackle this important issue.
Keywords: diversity in ophthalmology; mentorship; underrepresented minorities in medicine; pipeline program